Insurance status and demographic and clinical factors associated with pharmacologic treatment of depression: Associations in a cohort in Buenos Aires - MacHnicki, Gerardo (2011)
Objective: There is a paucity of evidence about insurance status and the likelihood of receiving medical services in Latin America. The objective of this analysis was to examine the association between insurance status and pharmacologic treatment for depression. Methods: Patients referred to a memory clinic of a public hospital in Buenos Aires, Argentina, and identified with any of four types of depression (subsyndromal, dysthymia, major, and due to dementia) were included. Age, years of education, insurance status, Beck Depression Inventory score, and number of comorbidities were considered. Associations between these factors and not receiving pharmacologic treatment for depression were examined with logistic regression. Use of prescription neuroleptics, hypnotics, and anticholinesterase inhibitors was also explored. Results: Out of 100 patients, 92 with insurance status data were used. Sixty-one patients (66%) had formal insurance and 31 patients (34%) lacked insurance. Twenty-seven (44%) insured patients and 23 (74%) uninsured patients did not receive antidepressants (P = 0.001). Controlling for other factors, uninsured patients had 7.12 higher odds of not receiving treatment compared to insured patients (95% confidence interval 1.8828.86). Older patients and those with more comorbidities had higher odds of not receiving treatment. More educated patients, those with higher Beck Depression Inventory score, and those without subsyndromal depression had lower odds of not receiving treatment. None of those associations were statistically significant. Conclusions: These results suggest a potential negative effect of the lack of formal insurance regarding pharmacologic treatment for depression. These findings should be confirmed with larger samples, and for other diseases.